Knowledge organization and information literacy in the digital world: a needed conversation - Francisco Javier García Marco (Informatio, 2025)
The interdisciplinary dialogue between knowledge organization and information literacy is examined and presented as a much-needed conversation. The viewpoint of the knowledge organization community is adopted as the central perspective, though both disciplines are considered. First, a prospective diagnosis of both disciplines is offered regarding their status for interdisciplinary cooperation, e.g., their basis for a fruitful dialogue. In the second step, the previous discussion on information literacy in the field of knowledge organization is examined in detail. Finally, it is concluded that information literacy must incorporate knowledge organization literacy with a careful consideration of the level of knowledge and needs of users. Conversely, information literacy can be helpful in knowledge organizations, and, in particular, knowledge organizations should consider information literacy as a key engine of their future disciplinary development and social relevance. Furthermore, knowledge organization systems and tools are effectively used to improve the user experience in information literacy actions and products, mainly taxonomies and ontologies in websites, assessment tools, and gamification projects.